Russian science and higher education: twenty years after - S. . Lebedev (Высшее образование в России)
The article analyzes the dynamics of Russian science and higher education during the last twenty years. The author strongly argues that the main characteristics of science developmentin Russia have considerably deteriorated. The fundamental problems and the possible ways their decisions are considered.